Analisis Kemampuan Berpikir Reflektif Siswa dalam Menyelesaikan Soal Cerita pada Materi Layang-Layang Ditinjau dari Gaya Belajar Siswa SMP Swasta Bukambero - Malo, Anjelina Deviana; Lede, Yulius Keremata; Making, Samuel Rex M. (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze students' reflective thinking skills in solving story problems on kite material reviewed from Visual, Auditory and kinesthetic learning styles. The method used in this study is descriptive qualitative. The subjects in this study were 15 students of grade VII of Bukambero Private Middle School. The subjects of the study were selected by purpose sampling by looking at the criteria for high, medium and low reflective thinking ability categories for each learning style. The object of this study is students' mathematical reflective thinking skills in solving story problems on kite material reviewed from learning styles. The data collection techniques used were Questionnaires/learning style questionnaires, reflective thinking ability tests, and interviews. Data analysis techniques used data reduction, data presentation and drawing conclusions. The results of the study using reflective thinking indicators showed that students with visual learning styles and students with Auditory learning styles were only able to meet the Reacting and comparing indicators, so this subject had moderate reflective thinking skills. while students with kinesthetic learning styles were able to meet all the Reacting, comparing and contemplating indicators. So it can be stated that students with kinesthetic learning styles have high reflective thinking skills compared to visual and auditory learning styles.